Terminology Data Processing: Model of the Dictionary of Librarianship, Information and Book Science - Bliūdžiuvienė, Nijolė; Černiauskaitė, Violeta (Knygotyra, 2021)
This paper focuses on terminological data identification, management, standardization and linguistic modeling techniques used in preparing a new model of the Lithuanian-English Dictionary of Librarianship, Information and Book Science at the Martynas Mažvydas National Library of Lithuania. This model is analysed from the point of view of current trends in terminology and standardization, and can expand knowledge exchange and help in its exchange accross these areas as well as improve the quality of professional content management in the future. Another aim of this paper was to update the importance of glossaries of technical terms for linguistic representation and global digital dissemination of scientific data in Lithuanian. This can help improve the quality of librarianship, information and communication knowledge, publicity, and wider use.
Keywords: terminological data; glossary of terms; lexicography; terminology; communication and information; information and documentation; book science; librarianship